PERBEDAAN KEKERASAN EMAIL PADA PERENDAMAN MINUMAN BERSODA DAN ISOTONIK DI MAKASSAR TAHUN 2018 - Syamsiah Syam; Nurasisah Lestari; Hikmah Syahrida Wahyuni Putri (As-Syifaa Jurnal Farmasi, 2018)
Background : Email is the most outer layer of the teeth, harder compared with the layer below which is dentin. Email hardness  is a physical conditions that belongs of the part of dental, it’s called email that can be measured using Vicker Hardness Tester by Kg/mm. Soft drink and isotonic is consisting of various types of a acids that lower of pH in oral cavity.  Objective : To know the difference of email hardness which is soaked in soft drink and isotonik.Method : Teeth post extraction, then soaked in to soft drink and isotonik for 2 hours. After that measured email hardness using Vicker Hardness Tester.Result : Based on Independent Sample T-test result the difference of email hardness which is soaked in soft drink and isotonic in Makassar 2017 obtained value of soft drink decreased of the email hardness  with value p = 0,662. Conclusion : Showed there’s a difference email hardness which is soaked in soft drink and isotonic, while the result of email hardness decreased between soft drink and isotonic there’s no significant difference.